2002
DOI: 10.1002/1521-3951(200211)234:2<665::aid-pssb665>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic Line Shift and Linewidth of the Raman Modes in GaS0.75Se0.25 Layered Crystals

Abstract: PACS: 63.20.Ry; 78.30. Hv The frequencies and linewidths of five Raman-active modes in a GaS 0.75 Se 0.25 layered crystal have been measured in the 10-300 K temperature range and in the 10-380 cm --1 frequency region. We observed softening and broadening of the optical phonon lines with increasing temperature. The analysis of the experimental data showed that the temperature dependencies of frequencies and linewidths are well described by considering the contributions from thermal expansion and lattice anha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The thermally softened Raman optical mode was attributed to the anharmonic-phonon decay to the third 6 or to the fourth 7 order in addition to the effects of thermal expansion [8][9][10][11] and/or interface effect, 12-14 as shown by…”
Section: Introductionmentioning
confidence: 99%
“…The thermally softened Raman optical mode was attributed to the anharmonic-phonon decay to the third 6 or to the fourth 7 order in addition to the effects of thermal expansion [8][9][10][11] and/or interface effect, 12-14 as shown by…”
Section: Introductionmentioning
confidence: 99%
“…Later, the effect of thermal expansion in Δ 2 was considered . Some works have shown that good reproduction of the measured T dependence of the red-shift of Raman optical phonon could be reached without considering the effect of thermal expansion. ,,,,, However, some calculations indicated that thermal expansion also played a certain non-negligible role in the T -induced red-shift of the Raman frequency. ,,, Sometimes the temperature-dependent strain induced by lattice and thermal mismatch between the specimen and the substrate became essential when the interface effect was considered, and this is represented by Δ 3 . ,, From the quantum mechanical point of view, the T -induced Raman red-shift can be fitted to a Bose−Einstein population as indicated by Δ 4 . , On the other hand, the first principle ab initio calculations have also been conducted to calculate some of the individual terms in eq 2 and then added up to examine the factors dominating the temperature dependence on the Raman modes.…”
Section: Introductionmentioning
confidence: 99%
“…PL spectra showed the presence of two PL bands centered at 527 and 658 nm at T = 10 K. Analysis of PL data revealed the origin of these bands as radiative transitions from shallow donor levels located at 0.043 and 0.064 eV to the acceptor levels at 0.088 and 0.536 eV, respectively. The frequencies and linewidths of Raman-active modes in GaS 0.75 Se 0.25 layered crystal have been measured in the 10-300 K temperature range and in the 10-380 cm À1 frequency region [11]. GaS 0.75 Se 0.25 single crystals were also studied by thermally stimulated current (TSC) measurements in the temperature range of 10-150 K [12].…”
Section: Introductionmentioning
confidence: 99%